Etika Berbahasa Generasi Z di Platform 'X' - Putri Nur’Aini, Alya; Artika Devi, Neta; Eka Maharani Putri, Silvia; Primakusuma W, Angela; Shafira Ramadhani, Nasywa; Puspa Arum, Dewi (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
This research aims to examine the evolving dynamics of language ethics among Generation Z, focusing on their communication behaviors on the "X" platform. Through a combination of case studies and discursive analysis, the study investigates emerging trends such as the increasing preference for informal expressions, the heightened use of abbreviations and emojis, and the shift toward a more expressive and casual digital communication style. Furthermore, the research delves into the broader implications of these linguistic trends, including their impact on social interactions, the shaping of public opinion, and the potential for misunderstandings in digital conversations. By exploring these phenomena, the study seeks to shed light on the underlying principles of digital communication among youth and how these behaviors influence their social lives, cultural norms, and the broader societal discourse. Ultimately, the findings aim to contribute to a deeper understanding of the interplay between digital language practices and the evolving nature of human connectivity in a digitally mediated world.